M13 Manchester lung cancer screening, targeting high-risk individuals in deprived areas of the community: results from the first incidence round of screening (1 year). (December 2018) - Balata, H; Crosbie, P; Barber, P; Colligan, D; Evison, M; Sharman, A; Tonge, J; Booton, R
Abstract : Background: The European position on lung cancer screening (LCS) recommends planning for implementation of low-dose computer tomography (LDCT) screening for lung cancer (LC) to start. The Manchester LCS pilot is one of the first NHS screening implementation programmes to take place and publish results. In this abstract we share results from the first incidence round of screening. Methods: Details of the baseline round of the Manchester LCS pilot have been previously published. 1 In brief, ever smokers, aged 55–74, from deprived areas were invited to a free 'Lung Health Check' (LHC) in mobile units located at their local shopping centres. The PLCOm2012 LC risk model was incorporated into the LHCs and those at high risk (PLCOm2012 ≥1.51%) were invited for annual screening starting with an immediate LDCT in a co-located mobile scanner. At baseline, 1384 individuals were screened and 3% had LC diagnosed (80% early stage, I-II). In the second round of screening, the first incidence round, all individuals screened at baseline with no subsequent diagnosis of LC (screening or non-screening) were invited back for an annual LDCT at the same community location. Exclusion included death, other malignancies and CT thorax within 3 months of due screening date. National and GP registries were checked for interval LC diagnosis. Results: A total of 1, 194 LDCT scans were performed as part of the second round of screening. 29 (2.4%) individuals received a positive scan result of which 19 (1.6%) were diagnosed with LC. 79% of LCs were early stage (I-II). The false positive rate was 0.8% of the screened population and 35% of those with a positive scan result. There were no interval LCs diagnosed at one year. Overall, 61 individuals (4.4%) have been diagnosed with LC (80% early stage) in the first 12 months of the Manchester LCS programme. Conclusion: Annual LDCT screening of high risk individuals in this real world LCS implementation pilot continues to identify a significant number of early stage lung cancers amenable to curative treatment. No interval lung cancers were diagnosed between rounds suggesting the baseline selection criteria for screening was appropriate. Reference: Crosbie PA, Balata H, et al. Implementing lung cancer screening: Baseline results from a community-based 'Lung Health Check' pilot in deprived areas of Manchester. Thorax2018.